The family support systems operating in the Visegrad Group countries (V4) - Csilla CZEGLEDI; Lukasz TOMCZYK; Alena CARVASOVA; Petr REHOR; Michaela SLADKAYOVA; Juhasz TIMEA (Eastern Journal of European Studies, 2022)
This study presents the family support systems that operate in the Visegrad Group countries: Hungary, Slovakia, the Czech Republic and Poland. After the collapse of communism, all four countries faced difficulties regarding the willingness of the population to have children, which was due partly to financial problems and to a slow re-evaluation of traditional roles in certain member states. Statistics show that each government strives to apply a number of similar support systems to encourage people to have children. However, these measures are not always efficient, presenting lower-than-expected results. According to the statistics available, fertility rates in the V4 countries still fall below the values of the 1990s.